Airbrush encapsulation of Lactobacillus rhamnosus GG in dry microbeads of alginate coated with regular buttermilk proteins. (January 2020) - Hugues-Ayala, Alma Mireya; Sarabia-Sainz, José Andre-i; González-Rios, Humberto; Vázquez-Moreno, Luz; Ramos-Clamont Montfort, Gabriela
Abstract: Lactobacillus rhamnosus GG ( L. rhamnosus GG) loaded calcium alginate microbeads were prepared via an airbrush system and subsequently coated with regular butter milk proteins (RBMP). Scanning electron micrographs and changes in zeta potential demonstrated the presence of RBMP on microbeads surface. Survivability of probiotics after microbead lyophilization was higher in coated microbeads (8.91 ± 0.03 log cfu) than in the uncoated ones (7.67 ± 0.09 log cfu). After storage at −20 °C for 30 d, the coated and uncoated microbeads showed 0.4 log and 0.8 log cfu/g loss in cell number, respectively. RBMP also enhance the survival of L. rhamnosus GG after exposure to sequential simulated gastrointestinal conditions. These results suggest that coating alginate capsules with RBMP is an effective strategy for the survival of L . rhamnosus GG when encapsulated with an airbrush system. Highlights: Lactobacillus rhamnosus GG were encapsulated in alginate via airbrush encapsulation. Airbrush system allowed the production of microbeads with recommended sizes to improve probiotic survival. Microbeads were coated with Regular Buttermilk Proteins (RBMP). RBMP coating protects encapsulated cells in simulated gastrointestinal conditions.